Predicting spectrums of adult mania, psychosis and depression by prospectively ascertained childhood neurodevelopment - Betts, K.; Williams, G.; Najman, J.; Alati, Rosa (2016)
© 2015 Elsevier Ltd. Background: We used a novel approach to investigate early neurodevelopmental factors of later adult spectrums of mania, depression and psychosis as a means to identify etiological similarities and differences among the three constructs. Methods: Participants were from the Mater University Study of Pregnancy (MUSP), a pre-birth cohort study started in Brisbane, Australia in 1981. A range of neurodevelopmental variables were ascertained at age 5, including measures of cognitive ability, developmental delay and behaviour problems. At age 21, offspring were assessed using a semi-structured psychiatric interview. We used structural equation modelling to establish three latent factors of mania, depression and psychotic symptoms. We then regressed these factors on the neurodevelopmental variables and covariates. Results: In both univariate and multivariate analysis premorbid cognitive ability predicted only psychotic symptoms, developmental delay predicted only manic symptoms, while behaviour problems predicted both depressive and psychotic symptoms. In a supplementary analysis the three factors were also found to have unique relationships with a number of outcomes also measured at age 21, including anxiety and substance use. Conclusion: By assessing the impact of early childhood neurodevelopment on the continuous spectrums which underlie three serious adult psychiatric disorders in a general population sample, we provide unique evidence regarding potential etiological similarities and differences. Perhaps of most interest is that our findings suggest that the manic and depressive symptoms in bipolar depression, despite often overlapping in clinical presentations, may in fact be somewhat separate entities with origins that are at least partly unique to either disorder.